Pulling it together. - Osborn, Marty (American City & County, 2007)
The article focuses on the benefits of linking the geographic information system (GIS) with Enterprise Asset Management (EAM) software to local governments. EAM offers information about infrastructure conditions, history and upcoming maintenance requirements. Several departments can see others' assets and coordinate maintenance tasks more easily if GIS will be linked to EAM. Open application program interfaces (APIs) will be needed to link information stored in an EAM with GIS data.